Combined cancer therapy with hyaluronan-decorated fullerene-silica multifunctional nanoparticles to target cancer stem-like cells. (August 2016) - Wang, Hai; Agarwal, Pranay; Zhao, Shuting; Yu, Jianhua; Lu, Xiongbin; He, Xiaoming
Abstract: Cancer stem-like cells (CSCs) are resistant to chemotherapy and highly tumorigenic, which contributes to tumor occurrence and post-treatment relapse. We developed a novel C60 fullerene-silica nanoparticle system surface-decorated with hyaluronan (HA) to target the variant CD44 overexpressed on breast CSCs. Furthermore, doxorubicin hydrochloride (DOX) and indocyanine green (ICG) can be encapsulated in the nanoparticles with ultrahigh encapsulation efficiency (>90%) and loading content (e.g., 48.5% at a drug-to-nanoparticle feeding ratio of 1:1, compared to the commonly used drug-to-nanoparticle feeding ratio of 1:20 with a drug loading content of less than 5%). As a result, the DOX and ICG-laden nanoparticles can be used as a single nanoplatform to achieve combined chemo, photodynamic, and photothermal therapy under near infrared laser irradiation for effective destruction of the breast CSCs both in vitro and in vivo, with no evident systemic toxicity. Moreover, we found the nanoparticles with a higher drug loading content (e.g., 48.5 versus 4.6%) also have significantly higher antitumor efficacy, given the same total drug dose. These results demonstrate the great potential of the multifunctional hybrid nanoparticle system for augmenting cancer therapy by eliminating the CSCs.